Managing Education for Economic Growth in India - Dawar, Kewal Raj (Gyan Management Journal, 2007)
The modem economy is a knowledge economy. In the post-independence period, the state promoted education with a view to create and expand knowledge for the purpose of social and economic development of the country. The importance of knowledge is being increasingly realized and it has taken the shape of an independent factor of production. Improvement in the quantity and quality of knowledge certainly enhances the productivity of other inputs such as labour, capital and organization, which can be further helpful in raising the economic strength of the nation. Education as a medium of explicit knowledge is instrumental in accelerating the socio-economic transformation of the country. In the emerging knowledge era, building a strong human capital is essential to complement and supplement the natural and physical resources of the country and education as a source of human resource development, ensures the availability of human capital of fine quality.
Keywords: Managing Education; knowledge economy; human resource development